MODUL BAHASA INGGRIS UNTUK PEMANDU WISATA KONSERVASI PENYU, MEMBANTU MASYARAKAT DALAM MELESTARIKAN PENYU LAUT - Dika Pranadwipa Koeswiryono; I Made Krisna Adi Chandra (English Language Education Department, Universitas Kristen Duta Wacana (UKDW), Yogyakarta, Indonesia, 2021)
Most of the six species of sea turtles in Indonesian waters have seen a decline, mainly due to human exploitation. One of the efforts to prevent the extinction of this pre-historic reptiles is the establishment of conservation centers. In Bali, one of the conservation centers actively involved in the efforts to conserve turtles is the Turtle Conservation and Education Center (TCEC). As more foreign tourists who are aware of turtle conservation come to this place, guides at TCEC are expected to able to provide sufficient explanation about turtles and their environment in English. They should provide a thorough insight of the turtle's anatomy, behavior, and reproductive cycle. This study aimed at developing English module for turtle conservation guides at TCEC. In developing the module, a framework of material development model was adopted. The framework consists of some stages namely, needs analysis, formulation of goals and objectives, development of English learning materials, and evaluation. The results of this study provide some implication and contributions for English language teaching.